1999
DOI: 10.1017/s0043174500092079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage systems, N, and cover crop on the composition of weed flora

Abstract: The adoption of conservation tillage systems has been challenged by concerns potential weed species shifts. A 9-yr study from 1988 to 1996 was conducted Delhi, Ontario, on a loamy sand soil to evaluate the effect of tillage systems (conventional [CT] and no-till [NT]), cover cropSecale cereale, and nitrogen (N) rate (0, 50, 100, 125, 150, and 200 kg N ha−1) on monocropZea maysL. (corn) yield and changes in the composition of the weed flora. CT consisted of spring moldboard plowing followed by cultivation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 52 publications
(35 reference statements)
12
81
0
Order By: Relevance
“…Increases in diversity of species under NT have been predicted because the successional process of the weed community is allowed to proceed further than under conventional tillage (Swanton et al, 1999;Chauhan et al, 2012). In accordance with this postulate, the cumulative effects of conservation tillage techniques (NT and MT), in our study, increased the weed density and species diversity in soil persistent weed seed bank compared to conventional tillage technique, whereas the vertical seed distribution did not show significant differences.…”
Section: Source Of Variation Soil Parameterssupporting
confidence: 86%
“…Increases in diversity of species under NT have been predicted because the successional process of the weed community is allowed to proceed further than under conventional tillage (Swanton et al, 1999;Chauhan et al, 2012). In accordance with this postulate, the cumulative effects of conservation tillage techniques (NT and MT), in our study, increased the weed density and species diversity in soil persistent weed seed bank compared to conventional tillage technique, whereas the vertical seed distribution did not show significant differences.…”
Section: Source Of Variation Soil Parameterssupporting
confidence: 86%
“…The corn yield increase in plots where barley cultivar Athinaida had incorporated is in agreement with findings of Shrestha et al (2002) who reported that soybean yield was increased by the presence of rye and corn used as cover crops. Also, Swanton et al (1999) found that corn yield was increased by a rye cover crop and Moore et al (1994) reported that soybean yield of the rye and triticale mulch treatments were 69 and 91% greater, respectively, than the bare soil treatment. The different effect of barley cultivar Athinaida on corn yield, compared with those of the other winter cereals tested, could be attributed to its stronger effect on grass weed emergence and growth.…”
Section: Resultsmentioning
confidence: 99%
“…In 1990, rainfall was above normal in May and early June but was near normal after mid-June (Table 2). In general, the same weed species were found on a given farm in both years (Table 4) 15 , because of differences in selection regimes and growth conditions, but there are no unique problems presented by ridge-tillage in this respect, and the weed species recorded here are commonly found throughout the state.…”
Section: Resultsmentioning
confidence: 58%